Pengaruh Kompetensi Sosial Guru PAK terhadap Prestasi Belajar Siswa dalam Pendidikan Agama Kristen - Yulianto, Auw Tammy; Kuntari J, Valentina Dwi; Sarumpaet, Sorimuda (PT. Bangun Harapan Bangsa, 2022)
This study aims to find out the relationship between the social competence of PAK teachers and the student achievement. The research was conducted at a Christian Vocational School, with students as the research subjects. The research population was 104 people, and the sample was obtained from 51 people. The research method used is descriptive quantitative method with correlational type of research. The data obtained were analyzed using correlation techniques and carried out with the help of the SPSS 13 computer program. The results of the analysis were that the perception of teachers' social competence was mostly assessed in a good category and most of the students' achievement in Christian religious education was in the good category. Thus, it can be concluded that the social competence of teachers has an influence on the learning achievement of Christian religious education of the students. The regression equation obtained is Y = 26.478 + 0.407 X